Action and resistance mechanisms of antibiotics: A guide for clinicians - Garima Kapoor; Saurabh Saigal; Ashok Elongavan (Journal of Anaesthesiology Clinical Pharmacology, 2017)
Infections account for a major cause of death throughout the developing world. This is mainly due to the emergence of newer infectious agents and more specifically due to the appearance of antimicrobial resistance. With time, the bacteria have become smarter and along with it, massive imprudent usage of antibiotics in clinical practice has resulted in resistance of bacteria to antimicrobial agents. The antimicrobial resistance is recognized as a major problem in the treatment of microbial infections. The biochemical resistance mechanisms used by bacteria include the following: antibiotic inactivation, target modification, altered permeability, and “bypass” of metabolic pathway. Determination of bacterial resistance to antibiotics of all classes (phenotypes) and mutations that are responsible for bacterial resistance to antibiotics (genetic analysis) are helpful. Better understanding of the mechanisms of antibiotic resistance will help clinicians regarding usage of antibiotics in different situations. This review discusses the mechanism of action and resistance development in commonly used antimicrobials.